An approach to the importance of tourism - Julca Meza, Ema Carmen (2017)
UNWTO defines tourism as the sum of relationships and services; tourism creates the interrelationshipsof social significance, but mainly creates economic interrelationships, so this has become the engine of tourism work and one of the most important economic activities in several countries, in which the tourism not only impacts the own economic sector, but also influences the results of other sectors, the quality of life of the inhabitants and their social development and conservation attractions.